ANALISIS KONTRASTIF KLAUSA VERBAL BAHASA ARAB DAN BAHASA INDONESIA SERTA IMPLIKASINYA DALAM PENGAJARAN NAHWU - Maman Abdurrahman (Sunan Kalijaga State Islamic University Yogyakarta, 2012)
This study was conducted to gain an overview of aspects of the similarities and differences between verbal clause in Arabic and verbal clauses in Indonesian. The object of the problem focused on a single clause types in terms of construction and sequence patterns of syntax and functionality is limited to verbal clauses: 1) eka/ monotransitif, 2) dwi/bitransitif, 3) the transitive-taktransitif, 4) semi-transitive, 5) untransitive, and 6) prepositional. In this study used a comparative method-konstrastif with emphasis on contrastive terms. Source data used as study materials in this study refers to the eight books of grammar / syntax: four Arabic books and four books in Indonesian language. From the eighth book was drawn patterns or examples and clauses are selected purposively in accordance with the aims and interests of this study. Then the processed data observations in a qualitative way through seven steps, namely 1) description, 2) selection, 3) contrast, 4) interpretation, 5) conclusion, 6) prediction, and 7) implications. Based on data analysis can be concluded there are aspects of similarity and syntactic differences between Arabic language and Indonesian language clause in terms of construction and function of the sequence pattern syntax.